Processing of Super Tough Plasticized PLA by Rotational Molding. (3rd February 2019) - Greco, Antonio; Ferrari, Francesca; Maffezzoli, Alfonso
Abstract : This work is aimed at studying the suitability of polylactic acid (PLA) plasticized by two cardanol derivatives, i.e., cardanol and epoxidized cardanol acetate, in rotational molding, for the production of hollow items. For this purpose, plasticized PLA samples were obtained by melt mixing and then processed by a lab-scale rotational molding equipment. For comparison, poly(ethylene glycole), PEG, and plasticized PLA samples were also produced. Despite the very low cooling rates attained in rotational molding, completely amorphous samples were obtained with neat PLA and PLA plasticized by cardanol derivatives. In contrast, PEG plasticized PLA showed a very high degree of crystallinity, as highlighted by DSC and XRD analysis, which made the extraction of the rotomolded box-shaped specimens impossible. The plasticizing effectiveness of cardanol derivatives was proven by tensile testing of rotational molded prototypes, which highlighted the reduced modulus and strength and improved strain to break, compared to neat PLA. Therefore, efficient toughening of PLA can be attained by the use of the two cardanol derived plasticizers, which involves a significant reduction of the polymer glass transition, as well as a reduced increase of the crystallization kinetic. On the other hand, the reduction of the glass transition temperature due to the addition of plasticizer is responsible for significant crystallization effects even during ageing at room temperature, which involves significant embrittlement of the material.